1Cr-1.25Mo-0.25V 강 잉곳의 응고편석 및 균질화 거동 - 김동배; Dong-bae Kim; 나영상; Young-sang Na; 서성문; Seong-moon Seo; 이재현; Je-hyun Lee (대한금속·재료학회지, 54(9), 2016)
As a first step to optimizing the homogenization heat treatment following high temperature upset forging, the solidification segregation and the homogenization behaviors of solute elements were quantitatively analyzed for 1Cr-1.25Mo-0.25V steel ingot by electron probe micro-analysis (EPMA). The random sampling approach, which was designed to generate continuous compositional profiles of each solute element, was employed to clarify the segregation and homogenization behaviors. In addition, ingot castings of lab-scale and a 16-ton-sized 1Cr-1.25Mo-0.25V steel were simulated using the finite element method in three dimensions to understand the size effect of the ingot on the microsegregation and its reduction during the homogenization heat treatment. It was found that the microsegregation in a large-sized ingot was significantly reduced by the promotion of solid state diffusion due to the extremely low cooling rate. On the other hand, from the homogenization point of view, increasing the ingot size causes a dramatic increase in the dendrite arm spacing, and hence the homogenization of microsegregation in a large-sized ingot appears to be practically difficult.(Received November 18, 2015; Accepted March 17, 2016)